SISTEM PENJAMINAN MUTU INTERNAL DAN EKSTERNAL PADA LEMBAGA PENDIDIKAN TINGGI - Muhammad Fadhli (JURNAL AL-TANZIM, 2020)
This study aims to portray internal and external quality assurance at higher education institutions, and the purpose of implementing quality assurance at educational institutions. In obtaining the data, this study used a library based qualitative approach by collecting data from books, journals, and articles. Based on the content analysis of the data, this study found that internal quality assurance includes: 1) policies and procedures for quality assurance; 2) approval, monitoring and periodic review of programs and awards; 3) student assessment; 4) quality assurance of teaching staff / lecturers; 5) resources student learning and support; 6) information systems; 7) public information. The external quality assurance includes: 1) use of procedures; 2) process development; 3) criteria for decisions; 4) processes in accordance with objectives; 5) reporting; 6) follow-up procedures; 7) periodic implementation reviews; and 8) system-wide analysis. The five objectives for quality assurance in educational institutions are improvement, innovation, communication, motivation, and control.